2016
DOI: 10.1016/j.acra.2016.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Texture-based Quantification of Centrilobular Emphysema and Centrilobular Nodularity in Longitudinal CT Scans of Current and Former Smokers

Abstract: Rationale and Objectives The effect of smoking cessation on centrilobular emphysema (CLE) and centrilobular nodularity (CN), two manifestations of smoking-related lung injury on CT images, has not been clarified. The objective of this study is to leverage texture analysis to investigate differences in extent of CLE and CN between current and former smokers. Materials and Methods Chest CT scans from 350 current smokers, 401 former smokers, and 25 control subjects were obtained from the multicenter COPDGene St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
(42 reference statements)
0
5
0
2
Order By: Relevance
“…In addition to the oncologic applications, there are a number of emerging nononcologic applications of CTTA, including assessing lung disease such as fibrosis and emphysema (11,(70)(71)(72)(73), assessing hepatic fibrosis (Fig 13) (13,74) or risk for hepatic failure after resection (9), assessing abdominal aortic aneurysms for risk of rupture (75), and evaluating osseous trabecular texture to detect anorexia nervosa (76). The number of studies is too limited to draw conclusions about the value of CTTA in assessing diffuse disease of the lungs and liver.…”
Section: Nononcologic Applications Of Cttamentioning
confidence: 99%
“…In addition to the oncologic applications, there are a number of emerging nononcologic applications of CTTA, including assessing lung disease such as fibrosis and emphysema (11,(70)(71)(72)(73), assessing hepatic fibrosis (Fig 13) (13,74) or risk for hepatic failure after resection (9), assessing abdominal aortic aneurysms for risk of rupture (75), and evaluating osseous trabecular texture to detect anorexia nervosa (76). The number of studies is too limited to draw conclusions about the value of CTTA in assessing diffuse disease of the lungs and liver.…”
Section: Nononcologic Applications Of Cttamentioning
confidence: 99%
“…This technique has been most intensely studied in oncologic applications, and has shown association with pathologic features and clinical outcomes in a variety of tumor types [18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Some non-oncologic applications are being evaluated, with several groups using texture analysis to assess emphysema and fibrosis in the lung [32,33]. One small series using CT texture analysis to evaluate hepatic fibrosis found that texture parameters showed some ability to discriminate between stages of fibrosis, but the results were not very convincing [34].…”
Section: Introductionmentioning
confidence: 99%
“…Neben den genannten Anwendungen der CT-Texturheterogenitätsanalyse im onkologischen Setting sind auch nicht maligne Erkrankungen ein möglicher Anwendungsbereich. So konnten beispielsweise strukturelle Lungengerüstveränderungen wie Emphysem und Fibrosegrade mittels 3D-CT-Texturanalyse robust charakterisiert werden [24,25]. Es besteht zudem potentiell die Möglichkeit nicht-invasive Diagnostiken auszuweiten, beispielsweise im Rahmen der Evaluation fibrotischer Leberparenchymveränderungen anhand von kontrastmittelgestützten CT-Scans [26].…”
Section: Statistik Ersterunclassified